Desertification and Agrifood Systems: Restoration of Degraded Agricultural Lands in the Arab Region - Feras Ziadat; Giulia Conchedda; Fidaa Haddad; Jeremiah Njeru; Aurélie Brès; Mona Dawelbait; Lifeng Li (Agriculture)
The FAO estimates that 1660 million hectares globally are degraded due to human activities, with over 60% of this degradation affecting agricultural lands, including croplands and pastures. Given that 95% of global food production depends on land, this widespread degradation presents significant challenges to agrifood systems. This study compares patterns of human-induced land degradation in Arab countries with global and regional averages, examining drivers, impacts on agrifood systems, current yield gaps, and restoration opportunities. The results indicate that in the Arab region, two-thirds of the 70 million hectares affected by human-induced degradation—over 46 million hectares—are agricultural land, with croplands particularly impacted. However, with less than 4% of land in the Arab region designated for restoration, the region lags behind global targets. Restoring 26 million hectares of degraded cropland could reduce the yield gap by up to 50% for oil crops and help cereal, root, and tuber crops approach their potential yields. These findings underscore the pressing need for a regional initiative specifically targeting agricultural land degradation to enhance food security, reduce poverty, and support sustainable and resilient agrifood systems.